Pengaruh Good Corporate Governance Dengan Likuiditas Dan Ukuran Perusahaan Sebagai Variabel Kontrol Terhadap Profitabilitas - Aminin, Auliya Listiyana; Zahara, Inna; Sulistiyantoro, David (Jurnal Riset AKuntansi dan Bisnis, 2024)
This study aims to determine the effect of Good Corporate Governance on liquidity and company size as control variables on profitability in the financial sector of companies listed on the IDX for the 2019-2022 period. GCG measurement uses Managerial Ownership, Institutional Ownership, Audit Committee, and Independent Board of Commissioners. Liquidity is measured using the Current Ratio. Company size is measured using Ln (Total Asset). Profitability is measured using ROA.Based on the SPSS output results, partially managerial ownership, institutional ownership, audit committees, and independent commissioners affect the profitability of financial sector companies for the 2019-2022 period. The results of the F test show that ownership, institutional ownership, audit committee, and independent board of commissioners are controlled by liquidity, and company size simultaneously affects the profitability of financial sector companies for the 2019-2022 period.